2006
DOI: 10.1088/0953-4075/39/5/013
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetically induced grating in a three-level Ξ-type system driven by a strong standing wave pump and weak probe fields

Abstract: We have analysed the properties of an electromagnetically induced grating formed in a Ξ-type three-level atomic system in the presence of a standing wave pump and travelling wave probe fields at resonant and off-resonant two-photon absorption. We have also shown the validity of this grating in an inhomogeneously broadened regime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 36 publications
1
62
0
Order By: Relevance
“…The n th-order diffraction intensity is determined by Eq. (8), and sin θ nλ p ∕Λ. Since we will mainly be interested in the first-order diffraction, the first-order diffraction intensity is gained as…”
Section: Atomic Model and Relevant Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The n th-order diffraction intensity is determined by Eq. (8), and sin θ nλ p ∕Λ. Since we will mainly be interested in the first-order diffraction, the first-order diffraction intensity is gained as…”
Section: Atomic Model and Relevant Equationsmentioning
confidence: 99%
“…Originally, EIT systems were always set in the traveling-wave (TW) pattern to establish spatially homogeneous quantum coherence. Recently, the standing wave (SW) driving the system has been well adopted to modulate periodically atomic coherence in space, which is advantageous for both the generation of photonic band gaps (PBGs) [3][4][5][6] and the creation of electromagnetically induced grating (EIG) [7][8][9][10][11]. The EIT technique is utilized to achieve many applications, such as light propagation control [12][13][14][15], enhancement of resonant optical nonlinearity [16][17][18], and state transfer between light and atoms [19][20][21], just to mention a few.…”
Section: Introductionmentioning
confidence: 99%
“…These structures are also referred to as electromagnetically induced absorption gratings (EIAG) [14] or electromagnetically induced gratings [15]. Many researchers have been focused on the study of EIAG [14][15][16][17][18][19][20][21][22][23], that are based on EIT, with their potential applications in mind. EIAG may be utilized for diffracting and switching a probe field, and probing the optical properties of materials.…”
Section: Introductionmentioning
confidence: 99%
“…The great attention to EIG is due to its potential applications in significant fields such as all-optical switching and routing [2], probing material optical properties [4], atomic/molecular velocimetry [5], light storage [6,7], optical bistability realization [8], beam splitting and fanning [9], shaping a biphoton spectrum [10], developing novel photonic devices in semiconductor QW systems [11], and controlling multi-wave mixing signals via photonic band gap of electromagnetically induced absorption grating in atomic media [12]. It is shown that the intensity of higher-order diffractions could be enhanced in a three-level ladder type system [13]. The phase grating efficiency was also improved by using a microwave field in a doubledark-state atomic system [14].…”
Section: Introductionmentioning
confidence: 99%